COMPARATIVE ANALYSIS OF LOGISTICS OF STATIONARY RETAIL AND ONLINE COMMERCE - Yerniyazova Zhanat Nurakhmetovna,; Talapbaeva Gulnar Edilovna,; Makasheva Gulbanu Kabdizhanovna,; Galidenov Makhambet Eltaevich, (Academic Journal of Physical and Chemical Sciences, 2020)
The development of the scientific concept of the economic category “logistics of trade services” dictates the need for the formation of logistics systems of trade services, which should be based on two dominant components - this is the territorial component and the integral. The need to include a territorial component is explained by the fact that retail trade and public catering, working for a specific consumer, gravitate towards the places where their client is located. The second component, an integrated logistics tool, provides for a significant change in the objective function and the criteria for the optimality of logistics activities, which makes it possible to achieve maximum competitive advantages to ensure the implementation of development strategies of the trading industry as a whole. In times of progressive digital transformation and constant change, a continuous reorientation of stationary retail is indispensable in order to be successful in the future. The practical recommendations for action provide a guideline for the transformation of stationary retailing based on digital change processes. Various factors are taken into account, which is identified as critical success factors for stationary retail. These include a reorientation of the business model, the introduction of new digital technologies and data protection. In general, stationary retail must rethink the business model holistically and be open to radical innovations in order to be successful in the long term.